Dynamics of genome reorganization during human cardiogenesis reveal an RBM20-dependent splicing factory - Alessandro Bertero; Paul A. Fields; Vijay Ramani; Giancarlo Bonora; Galip G. Yardimci; Hans Reinecke; Lil Pabon; William S. Noble; Jay Shendure; Charles E. Murry (Nature Communications, 2019)
The spatial organization of the genome plays an important but unclearly defined role in gene regulation. Here, the authors integrate Hi-C, RNA-seq and ATAC-seq data to map cardiogenesis from pluripotent stem cells and describe an RBM20-dependent splicing factory assembling the TTN locus with other RBM20 targets.